Oral and pharyngeal phases of swallowing in removable complete denture wearers - Marina Rodrigues Montaldi; Cláudia Helena Lovato da Silva; Adriana Barbosa Ribeiro; Camila Borba de Araujo; Caroline Vieira Fortes; Roberto Oliveira Dantas (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: To compare swallowing and bolus transit time through the oral cavity and pharynx between well-fitted complete denture wearers and toothed individuals. Methods: Altogether, 27 complete denture wearers (43 to 77 years old) and 26 controls (41 to 74 years old) were examined with videofluoroscopic swallowing study using liquid, pureed, and solid (crackers and toasts) bolus, twice and in a random sequence. Denture wearers were assessed with and without dentures. Results: Individuals wearing dentures had oral residues after swallowing liquid (in 56% of swallows) and pureed boluses (in 71% of swallows) and with toasts (in 41% of swallows), more often than controls (liquid 13%, pureed 43% and toast 15% of swallows, p ≤ 0.04). In denture wearers, the oral, upper esophageal sphincter, and pharyngeal transit times were longer after swallowing liquid bolus; the pharyngeal and oropharyngeal transit times were longer after swallowing pureed bolus; and the oropharyngeal transit time was longer after eating crackers. Assessment results without dentures were closer to that of controls when swallowing pureed bolus. Laryngeal aspiration was not observed in any of the individuals. Conclusion: Removable complete denture wearers tend to have longer pharyngeal transit time than toothed individuals. Although oral residues and longer pharyngeal transit in individuals wearing dentures increase the risk of airway aspiration, this investigation did not verify such a condition.